DETERMINANTS OF COMMERCIAL BANKS PROFITABILITY: EVIDENCE FROM GERMANY - Szilard Farkasdi; Budi Septiawan; Erik Syawal Alghifari (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2021)
This study aims to determine the determinants of profitability in commercial banks in Germany. The population is 7 banking sector companies listed in the DAX (Deutscher Aktienindex) Bank during the 2017-2020 period, with a sample of 5 banks and producing 20 observational data. The method used is descriptive and verification with multiple regression analysis. The results show that asset size, capital adequacy, deposits and non-interest income have a significant positive effect on profitability. Partially, asset size, capital adequacy and non-interest income have a significant positive effect, while the deposit has a significant negative effect on profitability. The most dominant factor affecting profitability is non-interest income.